Genesis of the Formation of the Concept of Personal Freedom of Citizens: Historical and Legal Aspects - Kuchukov, Kairat; Zhugralin, Serik; Mussabekov, Yerubay; Bulekbayeva, Raziya; Syzdykova, Aigul (International Journal of Psychosocial Rehabilitation, 2020)
Consideration of the problem of ensuring personal freedom of citizens involves the study of many issues related, firstly, to the definition of the very concept of personal freedom of citizens from the perspective of philosophy and secondly, an analysis of the legal significance of this institution of the social structure of society. The problem seems to be quite global, and the large volume of research related to ensuring personal freedom of citizens, the state formulation of such issues, the constitutional consolidation of the basic tenets of a democratic state related to the definition of an individual citizen as well as his legal rights and interests as the main value of society are confirmation of this, including the right to personal freedom, the right to free choice of occupation. Defining the concept of personal freedom, personality, personal security and basic measures to ensure it, I would also like to touch on the philosophical aspect of the problem, since, as it seems to us, it would be wrong to leave this side of the issue untouched, since in many ways the development of problems of a legal level requires its own philosophical justification.